Pengaruh Risk Attitude, Risk Perception, dan Subjective Norm terhadap Risk Intended Behavior dari Restoran Makanan yang Tidak Memiliki Sertifikasi Halal bagi Konsumen Muslim, dengan Variabel Moderator Religiusitas - Rojib Burhan Winahyu (BISMA (Bisnis dan Manajemen), 2018)
Restaurant in East Java last few years has increased significantly, where they come to offer a wide  selection  of  new  and  exciting  menus  to  satisfy  consumers.  On  the  other  hand  a  lot  of publicity to grow, both through print and electronic media about the composition of the food in them contain components harmful to the health of the body as well , including the types of food that is prohibited for consumption by religious law ( especially for Muslims ) widely circulated and highly troubling . This phenomenon is reinforced with only three restaurants in East Java that has a halal certification. Of course it is ironic that the majority of the population in East Java is Muslim. It should be noted by the company restaurant food is how consumer behavior in the  face  of  such  phenomena.  Where  the  risk  is  influenced  consumer  behavior  from  attitudes towards risk (risk attitude), risk perception, subjective norms and consumer behavior in the face of  possible  risks  that  would  happen  (risk  behavior  intention)  of  restaurant  that  havent halal certification. This study using a quantitative design with statistical tools Partial Least Square (PLS). The results found that the risk attitude, risk perception, subjective norm effect on risk intention  behavior.  While  the  value  of  religiosity  a  person  does  not  give  effect  to  the relationship of risk attitude and risk perception on risk behavior intention